Evaluation of the Enterotube System for Identification of Members of the Family Enterobacteriaceae - Martin, William Jeffery (1971)
The Enterotube system was evaluated, in parallel with conventional bacteriological procedures for the identification of members of the family Enterobacteriaceae, by using bacterial strains from a variety of clinical specimens and from stock cultures. Excellent agreement between the two test systems was obtained with the following reactions: hydrogen sulfide, indole, Simmons' citrate, glucose, and lactose. Agreement was not as good (<85%) with the urea, phenylalanine deaminase, and dulcitol reactions. The Enterotube lysine decarboxylase test was unsatisfactory. The Enterotube method will correctly identify strains of the family Enterobacteriaceae approximately 50% of the time; if identification only as Klebsiella-Enterobacter-Serratia group is needed, the method will be correct 85% of the time. On the basis of this evaluation, the Enterotube system appears to be both simple and rapid for the presumptive identification of these bacteria. Because of the limited usefulness of the lysine decarboxylase test, the results obtained by this test system are less reliable than those obtained by conventional methods.